Liberalization and Regional Integration: The Philippines' Strategy to Global Competitiveness - Myrna S. Austria (Philippine Institute for Development Studies (PIDS), 2001)
The paper examines the policies pursued by the Philippines in response to the increasing economic integration and interdependence of nations and regions around the world, focusing in particular on the countrys multi-track approach to trade and investment liberalization. The countrys experience points to the importance of domestic policies that foster domestic efficiency and competitiveness before one can participate in regional integration and face global competition. The country first pursued trade and investment liberalization policies in the 1980s and 1990s to eliminate the inefficiency of domestic industries arising from its past protectionist regime. The unilateral liberation efforts resulted to a better allocation of resources and improvement in the overall competitiveness of domestic industries. The improved competitiveness enabled the country to participate in the 1990s in regional trading arrangements, AFTA and APEC, and in the much bigger WTO. The challenge facing the country now is how to deepen and expand its participation in regional integration as the proliferation of regional trading arrangements has brought forth many new competitors for the country, both for its export markets and sources of foreign direct investment. Areas where further reforms are necessary are identified to enable the country to realize the full gains from economic integration.
Keywords: 330; globalization; trade liberalization; World Trade Organization; competitiveness; economic integration; ASEAN; regional integration; regional trading arrangements; interregional trade; ASEAN Free Trade Area (AFTA); global competition; multilateral cooperation; APEC; investment liberalization; Internationaler Wettbewerb; Handelsliberalisierung; Philippinen